Sehat Cerdas Dimulai dari Usia Dini Melalui Kebiasaan Hidup Sehat, Bersih, dan Rajin Mencuci Tangan Sebelum serta Sesudah Makan Pada sekolah MIS Raudhotul Mubtadiin Kelurahan Buaran Serpong Tangerang Selatan - Dian Esha; Fauzan Hakim (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Healthy and clean living behaviors are an important foundation for establishing children's health and well-being from an early age. One simple yet highly influential habit is washing hands before and after eating. This habit not only helps prevent the spread of germs and diseases but also instills values of discipline and awareness of personal hygiene. Early childhood is a crucial stage of development; therefore, the practice of clean and healthy living behaviors needs to be consistently encouraged through role modeling, guidance, and education from parents and teachers. The implementation of healthy and clean living practices can support children's physical growth, cognitive development, and character formation, helping them become a healthy and intelligent generation. Therefore, educating children about healthy living habits from an early age is a strategic step toward creating a high-quality and competitive generation in the future.